Acceptability of the Medication Adherence for Patients Support intervention to improve adherence to patients prescribed medications for hypertension or comorbidities, as an adjunct to primary care: A qualitative study. (January 2021) - Kassavou, Aikaterini; Houghton, Vikki; Edwards, Simon; Brimicombe, James; Wilson, Ed; Griffin, Simon; Sutton, Stephen
Tailored interventions delivered via text and voice messages can improve adherence to multiple medications. However, no such intervention has been developed in the UK primary-care setting. We conducted focus groups with 12 patients with hypertension, type 2 diabetes, or both conditions, presumed to be non-adherent and recruited from deprived neighborhoods, to assess the acceptability and inform the development of an intervention to provide ongoing support for adherence, as an adjunct to primary-care consultations. Patients recommended ways to improve the tailored content and delivery of the intervention; like highly interactive messages to report both medication taking and determinants of medication adherence.